2019
DOI: 10.1177/0300060519847367
|View full text |Cite
|
Sign up to set email alerts
|

Topical treatment of acne vulgaris: efficiency, side effects, and adherence rate

Abstract: Objective Adherence is a problem in the topical treatment of acne. This study was designed to evaluate the efficiency of current topical treatment and adherence in patients. Methods Patients with acne vulgaris who had recently been prescribed a topical therapy were selected. A dermatologist-directed questionnaire was completed. Demographic data, acne severity, treatment and the manner of use, side effects, and reason for discontinuation were recorded. Results A total 250 patients were included, 178 female (71.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 11 publications
2
56
0
3
Order By: Relevance
“…We also noticed that feeling a lack of treatment responsiveness is significantly associated with low adherence score. This was consistent with a study conducted by Sevimli et al in which unresponsiveness to medication was a common reason for discontinuation 31. Some types of dermatological treatments need a long period of time to start showing its positive effects.…”
Section: Discussionsupporting
confidence: 92%
“…We also noticed that feeling a lack of treatment responsiveness is significantly associated with low adherence score. This was consistent with a study conducted by Sevimli et al in which unresponsiveness to medication was a common reason for discontinuation 31. Some types of dermatological treatments need a long period of time to start showing its positive effects.…”
Section: Discussionsupporting
confidence: 92%
“…Looking on the adherence in topical acne therapy, it can be observed in the same manner the influence of adverse symptoms. Regarding an actual study of Sevimli Dikicier on 250 subjects in a clinical hospital from Turkey, the discontinuation of acne treatment was analyzed using questionnaires with key factors that influence the patient response to therapy [ 138 ]. It was observed that 45.6% of the subjects have abandoned the therapy, signaling that side effects or absence of visible effects are the main reasons for neglect [ 138 ].…”
Section: Current Topical Formulations In Acne Therapymentioning
confidence: 99%
“…Regarding an actual study of Sevimli Dikicier on 250 subjects in a clinical hospital from Turkey, the discontinuation of acne treatment was analyzed using questionnaires with key factors that influence the patient response to therapy [ 138 ]. It was observed that 45.6% of the subjects have abandoned the therapy, signaling that side effects or absence of visible effects are the main reasons for neglect [ 138 ]. To conclude, adherence can reach a high level when skin response to therapy is positive and rapidly obtained.…”
Section: Current Topical Formulations In Acne Therapymentioning
confidence: 99%
“…Вульгарные акне (acne vulgaris, ВА) являются одним из наиболее распространенных хронических воспалительных дерматозов с поражением сально-волосяного аппарата; заболевание характеризуется образованием открытых и закрытых комедонов, папул, пустул и/или узлов [1,2]. Развивающиеся в результате эволюции различных форм ВА вторичные высыпания, представляющие собой в большинстве случаев вторичную гиперпигментацию, рубцы, а также эритематозные пятна, атеромы и милиумы, носят название «симптомокомплекс постакне» [3].…”
Section: определение и эпидемиологияunclassified